Self-Reported General Health, Overall and Work-Related Stress, Loneliness, and Sleeping Problems in 335,625 Swedish Adults from 2000 to 2016 - Blom, Victoria (Int J Environ Res Public Health, 2020)
The prevalence of poor health, in particular stress-related mental ill-health, is increasing over time and birth cohorts. As rapid societal changes have occurred in the last decade and still are occurring, there is an interest in investigating the trends in health-related factors. The aim of the present study was to investigate trends in self-reported general health, overall stress, work-related stress, feelings of loneliness, and sleeping problems in 335,625 Swedish adults across categories of gender, geographic regions, length of education, and age from 2000 to 2016. On population level, sleeping problems and poor general health have increased markedly and significantly, while experiences of work stress decreased between 2000 and 2016 (p < 0.05). Overall stress and level of loneliness were unchanged (p > 0.05). The risk of having ≥3 symptoms (any of poor or very poor general health, often or very often perceived overall stress, loneliness, or sleeping problems) has increased significantly from 2000 to 2016 (ß = 1034 (1027–1040)). This increase was significantly higher in young (ß = 1052 (1038–1065)) and individuals with lower education (ß = 1056 (1037–1076)) compared to older and high length of education.